High-nitrogen superaustenitic stainless steel as-cast dendritic crystal corrosive agent and use method thereof

By using a mixed solution composed of nitric acid, hydrochloric acid, etc. as the corrosion agent and calculating the optimal corrosion conditions based on the element content, the problem of cast structure quality evaluation of high-nitrogen super austenitic stainless steel is solved, and a more uniform and accurate dendrite corrosion effect is achieved.

CN120210820APending Publication Date: 2025-06-27NORTHEASTERN UNIV CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510049197.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The prior art is difficult to effectively evaluate the cast structure quality of high-nitrogen super austenitic stainless steel, and the traditional dendrite corrosion method is not effective when the element content changes, and it is prone to corrosion too shallow or too deep.

Method used

A mixed solution composed of nitric acid, hydrochloric acid, oxalic acid, ferric chloride, sodium molybdate and copper chloride is used as the corrosion agent. The optimal corrosion agent ratio and time are calculated through empirical formulas to ensure the uniformity and integrity of the corrosion effect.

Benefits of technology

This method can calculate the optimal corrosion conditions based on the element content in the steel, significantly improve the corrosion effect, avoid the problem of too deep or too shallow corrosion, and provide a more accurate evaluation of dendrite structure of high-nitrogen super austenitic stainless steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120210820A_ABST
    Figure CN120210820A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of steel billet dendritic structure metallographic analysis, and relates to a high-nitrogen superaustenitic stainless steel as-cast dendritic crystal corrosive agent and a use method. The corrosive agent is a mixed solution of nitric acid, hydrochloric acid, oxalic acid, ferric chloride, sodium molybdate and copper chloride, wherein the concentrations of the oxalic acid and the ferric chloride are fixed at 1.1-1.3 g / L and 7.5-8.5 g / L; the concentrations of the sodium molybdate and the copper chloride are 9.0-11.0 g / L and 6.0-7.0 g / L respectively; the mass percentage concentrations of the nitric acid and the hydrochloric acid are 65-68% and 36-38% respectively, and the ratio of the nitric acid to the hydrochloric acid is determined according to the nitrogen content in the steel. According to the method, the optimal corrosive agent proportion and corrosion time can be calculated by utilizing an empirical formula according to the element content in the steel, the corrosion effect is greatly improved, the problem that corrosion is too deep or too shallow easily occurring in the corrosion process is solved, and the method has important significance on researching the dendritic crystal spacing and form of the high-nitrogen super austenitic stainless steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metallographic analysis of steel billet dendritic structure, and relates to a dendritic etchant for as-cast high-nitrogen super-austenitic stainless steel and a using method thereof. Technical Background

[0002] Super-austenitic stainless steel is a high-alloy stainless steel. By increasing the contents of alloying elements such as nickel and molybdenum, its corrosion resistance and toughness are improved. Its pitting corrosion resistance far exceeds that of ordinary austenitic stainless steel, and its pitting resistance equivalent number (PREN) is usually greater than 40. In addition, the high toughness of super-austenitic stainless steel enables it to maintain good mechanical properties in low-temperature environments and is not prone to brittle fracture. Due to its excellent corrosion resistance and high strength, super-austenitic stainless steel is widely used in fields such as chemical industry, petroleum, and ocean engineering. With the increasingly harsh service environments of high-end equipment, higher requirements are also put forward for the performance of super-austenitic stainless steel. In actual production, dendritic structure is an important parameter for evaluating the mechanical properties such as tensile strength, hardness, and toughness of materials and judging the uniformity of materials. The dendritic etching process for high-nitrogen super-austenitic stainless steel becomes extremely difficult due to its excellent corrosion resistance. Therefore, it is urgent to find a dendritic etching method that can be used for the quality evaluation of the as-cast structure of high-nitrogen super-austenitic stainless steel, which is of great significance for improving the quality control of high-nitrogen super-austenitic stainless steel.

[0003] At present, there are few reports on the dendritic etching method for high-nitrogen super-austenitic stainless steel, and the reported related dendritic etching methods have poor dendritic etching effects on high-nitrogen super-austenitic stainless steel.

[0004] Publication No. CN106596235A discloses "Dendritic Etchant for High-Nitrogen Austenitic Stainless Steel and Its Using Method". This method uses an etchant prepared from copper chloride, magnesium chloride, ferric chloride, water, hydrochloric acid, nitric acid, and absolute ethanol, and stands for 5 - 15 minutes and then etches for 2 - 5 minutes. The composition of the etching solution of this method is too complex, the etching time cannot be accurately controlled, and it is extremely easy to occur the situations of too shallow or too deep etching. And when the element content in the steel changes, the etching effect is often poor.

[0005] Publication No. CN114657563A discloses "IF Steel Metallographic Etchant and Etching Method". This method uses nitric acid alcohol and hydrogen peroxide for immersion etching for 10 - 50 s. This method has no accurate etching time, and it is also extremely easy to occur the phenomena of too deep or too shallow etching. And this method has poor etching effect on high-nitrogen and high-molybdenum steel.

[0006] Publication No. CN118360654A discloses "A Corrosive Agent and Corrosion Method for High-Nitrogen Austenitic Stainless Steel". This method uses perchloric acid with a volume fraction of 3% - 8% and alcohol with a volume fraction of 92% - 97% to prepare a corrosive agent, and applies an electric current for 2s - 40s under the condition of a voltage of 3v - 8v. When the element content in the steel changes, the corrosion effect of this method is often unstable, the corrosion time range is relatively large, and electrolytic corrosion is required, so the operation is relatively complex.

[0007] Most traditional corrosion processes cannot accurately obtain the corrosion time and are only effective for steel with a single content of a certain steel type. When the element content of the steel type changes, the corrosion effect is often poor. Summary of the Invention

[0008] In view of such problems, the present invention provides a corrosive agent and usage method for as-cast dendrites of high-nitrogen super-austenitic stainless steel.

[0009] The technical solution adopted by the present invention is as follows:

[0010] A corrosive agent for as-cast dendrites of high-nitrogen super-austenitic stainless steel, wherein the composition range of the high-nitrogen super-austenitic stainless steel is: C: ≤0.12%, Si: ≤0.71%, Mn: 3.0 - 11.0%, Cr: 16.0 - 25.0%, Mo: 4.0 - 10.0%, N: 0.3 - 1.6%, Ni: 14.0 - 23.0%, Cu: 0.2 - 0.6%, Fe: the balance. The corrosive agent is a mixed solution of nitric acid, hydrochloric acid, oxalic acid, ferric chloride, sodium molybdate and copper chloride, wherein: the concentrations of oxalic acid and ferric chloride are fixed at 1.1 - 1.3g / L and 7.5 - 8.5g / L; the concentrations of sodium molybdate and copper chloride are 9.0 - 11.0g / L and 6.0 - 7.0g / L; the mass percentages of nitric acid and hydrochloric acid are 65 - 68% and 36 - 38% respectively, and the ratio of nitric acid to hydrochloric acid is determined according to the nitrogen content in the steel and obtained from formula (1):

[0011] V 硝酸 : V 盐酸 = 0.06N 含 (1)

[0012] In the formula, V 硝酸 and V 盐酸 are the volumes of nitric acid and hydrochloric acid in the corrosive agent respectively, and N 含 is the nitrogen solubility in the steel block.

[0013] The usage method of the corrosive agent for as-cast dendrites of high-nitrogen super-austenitic stainless steel includes the following steps: (1) Prepare a high-nitrogen super-austenitic stainless steel block

[0014] The corroded high-nitrogen super-austenitic stainless steel blocks are hot-mounted using an embedding machine, and then polished successively with sandpaper and a polishing machine until the surface is smooth and shiny. Then, they are rinsed with deionized water and absolute ethanol and dried. Finally, they are observed under an optical metallurgical microscope to ensure that there are no scratches or depressions on the surface.

[0015] (2) Determine the correction coefficient β

[0016] The correction coefficient β is determined by the crystal region condition after mild corrosion, and generally takes values from 0.9 to 1.1. It takes 1.1 when the steel block is in the columnar crystal region, 1.0 when in the CET region, and 0.9 when in the equiaxed crystal region.

[0017] For mild corrosion, the corrosive agent is prepared from perchloric acid with a volume fraction of 7% - 9% and absolute ethanol with a volume fraction of 91% - 93%. The mass percentage concentration of perchloric acid is 70 - 72%.

[0018] The prepared mild corrosive agent is allowed to stand and react for 3 - 5 minutes. Subsequently, the prepared high-nitrogen super-austenitic stainless steel blocks are immersed in the mild corrosive agent, and the constant-temperature environment is set to 78 - 80 °C. The corrosion time is generally 50 s - 70 s. After the corrosion is completed, the steel blocks are taken out and rinsed thoroughly with deionized water and absolute ethanol and dried. The high-nitrogen super-austenitic stainless steel blocks after mild corrosion are placed under a metallurgical optical microscope to observe the crystal region characteristics, and then the correction coefficient β is determined. Then, the steel blocks after mild corrosion are remade according to step (1). (3) Prepare the as-cast dendritic corrosive agent for high-nitrogen super-austenitic stainless steel

[0019] Nitric acid, ferric chloride, oxalic acid, sodium molybdate, and copper chloride are successively added to hydrochloric acid and stirred thoroughly. The resulting solution is placed in a constant-temperature environment of 48 - 52 °C for full reaction for 15 - 20 minutes. When the solution turns light yellowish-green, it indicates that the solution reaction is complete, and the as-cast dendritic corrosive agent for high-nitrogen super-austenitic stainless steel is obtained. (4) Determine the constant-temperature heating corrosion time T

[0020] The constant-temperature heating corrosion time T is calculated from formula (2):

[0021] T = (18Ni 含 + 38Mo 含 + 505N 含 + 21Mn 含 ) × β (2)

[0022] In the formula, Ni 含 , Mo 含 , N 含 , Mn 含 are respectively the solubility of the element in the steel block, and the correction coefficient β has been calculated in step (2).

[0023] (5) Metallographic corrosion

[0024] Immerse the high-nitrogen super-austenitic stainless steel block in the corrosion agent in a constant-temperature environment and gently shake it to prevent bubbles from adhering to the surface of the steel block. The initial temperature of the constant-temperature environment during corrosion is generally set at 78 - 80 °C to accelerate the corrosion efficiency. At this temperature, the corrosion time is about 490 - 510 s. Subsequently, the temperature is set at 48 - 50 °C until the corrosion ends to ensure a good corrosion effect. After the corrosion ends, take out the steel block and rinse it thoroughly with deionized water and anhydrous ethanol in sequence, and then dry it. Observe its dendritic structure with a scanning electron microscope (SEM) or a metallographic optical microscope.

[0025] Compared with the existing corrosion process, this method can calculate the optimal corrosion agent ratio and corrosion time according to the element content in the steel by using an empirical formula, greatly improving the corrosion effect, solving the problem of excessive or insufficient corrosion during the corrosion process, and is of great significance for studying the dendrite spacing and morphology of high-nitrogen super-austenitic stainless steel. Description of the Drawings

[0026] Figure 1 It is the dendrite diagram after the corrosion of the high-nitrogen super-austenitic stainless steel block in Example 1;

[0027] Figure 2 It is the dendrite diagram after the corrosion of the high-nitrogen super-austenitic stainless steel block in Example 2;

[0028] Figure 3 It is the dendrite diagram after the corrosion of the high-nitrogen super-austenitic stainless steel block in Example 3;

[0029] Figure 4 It is the dendrite diagram after the corrosion of the high-nitrogen super-austenitic stainless steel block in Example 4;

[0030] Figure 5 It is the dendrite diagram after the corrosion of the high-nitrogen super-austenitic stainless steel block in Example 5;

[0031] Figure 6 It is the dendrite diagram after the corrosion of the high-nitrogen super-austenitic stainless steel block in Example 6;

[0032] Figure 7 It is the dendrite diagram after the corrosion of the high-nitrogen super-austenitic stainless steel block in Example 7. Detailed Embodiments

[0033] The embodiments of the present invention will be described in detail below in combination with the technical solutions and the drawings.

[0034] Example 1

[0035] In this example, the element content of the high-nitrogen super-austenitic stainless steel block is shown in Table 1

[0036] Table 1 Composition content of high-nitrogen super austenitic stainless steel block (wt%)

[0037] Component Cr Mn Ni Mo C Si Cu N Fe Content 24.5 6.00 17.0 5.50 0.02 0.40 0.50 0.40 Balance

[0038] First, the corroded high-nitrogen super austenitic stainless steel block is hot-mounted using a sample mounting machine, and then polished successively with 400-mesh, 800-mesh, 1200-mesh, 1500-mesh, and 2000-mesh sandpapers to remove the defects on the surface of the steel block. Then, a polishing machine, damping cloth, and polishing pastes of 3.5 μm and 2.5 μm are used for polishing respectively until the surface is smooth and shiny. After polishing, it is rinsed successively with deionized water and absolute ethanol, then air-dried with an air dryer, and finally observed with an optical metallographic microscope, with no scratches and depressions on the surface.

[0039] Secondly, a mild corrosive agent is prepared by mixing perchloric acid with a volume fraction of 8% and absolute ethanol with a volume fraction of 92%. Then, the prepared steel block is immersed in the mild corrosive agent, and the temperature of the constant temperature water bath heating box is set at 80 °C, and the corrosion time is 60 s. After corrosion, the steel block is taken out and rinsed thoroughly successively with deionized water and absolute ethanol, and finally air-dried with an air dryer. The mildly corroded high-nitrogen super austenitic stainless steel block is observed under a metallographic optical microscope at 139 times magnification for the crystal region, and it is found that the steel block is entirely located in the columnar crystal region. Therefore, the correction coefficient β is taken as 1.1. Then, the mildly corroded steel block is remade into a sample according to step (1).

[0040] Calculate V through empirical formula (1) 硝酸 : V 盐酸 The ratio is 0.024, where N 含 is 0.40. Generally, V 盐酸 is taken as 100 ml. Therefore, V 硝酸 is 2.4 ml. Then, 0.123 g of oxalic acid, 0.820 g of ferric chloride, 1.024 g of sodium molybdate, and 0.614 g of copper chloride are prepared according to the requirements of the concentrations of each component of the corrosive agent. The weighed nitric acid, ferric chloride, oxalic acid, sodium molybdate, and copper chloride are successively added to hydrochloric acid and continuously stirred with a glass rod to dissolve them fully. Then, the solution is placed in a constant temperature water bath heating box at 50 °C for full reaction. After 17 minutes, the solution turns light yellowish green, indicating that the solution reaction is basically complete.

[0041] The prepared steel block is clamped with a clip and immersed in the corrosive agent in the constant temperature water bath heating box, and gently shaken to prevent bubbles from adhering to the surface of the steel block. Then, the required water bath heating corrosion time is calculated to be 927.3 s through formula (2), where Ni 含 , Mo 含 , N 含 , Mn 含It can be obtained from Table 1. During corrosion, the initial temperature of the constant temperature water bath heating box is set at 80 °C according to experience. After 500 seconds, the water bath temperature is lowered to 48 °C. After the corrosion is completed, the steel block is taken out and rinsed thoroughly with deionized water and absolute ethanol in sequence, and finally dried with a hair dryer. The corroded steel block is photographed and observed under a metallurgical optical microscope at a magnification of 139 times. The dendrites of the steel block are as Figure 1 shown. From Figure 1 , the primary dendrites and secondary dendrites of the steel block can be clearly observed. The corrosion effect is uniform, complete and clear. It can be used for the preliminary analysis of the mechanical properties and uniformity of the high-nitrogen super austenitic stainless steel block, and can also be used for the statistics of the secondary dendrite spacing.

[0042] Example 2

[0043] In this example, the element content of the high-nitrogen super austenitic stainless steel block is shown in Table 2

[0044] Table 2 Composition content (wt%) of high-nitrogen super austenitic stainless steel block

[0045] Component Cr Mn Ni Mo C Si Cu N Fe Content 24.5 4.00 17.0 5.50 0.02 0.40 0.50 1.00 Balance

[0046] First, the corroded high-nitrogen super austenitic stainless steel block is hot-mounted with an embedding machine, and then polished successively with 400-mesh, 800-mesh, 1200-mesh, 1500-mesh, and 2000-mesh sandpapers to remove the defects on the surface of the steel block. Then, a polishing machine, damping cloth, and polishing pastes of 3.5 μm and 2.5 μm are used for polishing respectively until the surface is smooth and shiny. After polishing, it is rinsed with deionized water and absolute ethanol in sequence, and then dried with a hair dryer. Finally, it is observed with an optical metallurgical microscope, and there are no scratches and defects on the surface of the steel block.

[0047] Secondly, a mild corrosive agent is prepared by mixing perchloric acid with a volume fraction of 8% and absolute ethanol with a volume fraction of 92%. Then, the prepared steel block is clamped and immersed in the mild corrosive agent. The temperature of the constant temperature water bath heating box is set at 79 °C, and the corrosion time is 61 s. After the corrosion is completed, the steel block is taken out and rinsed thoroughly with deionized water and absolute ethanol in sequence, and finally dried with a hair dryer. The mildly corroded high-nitrogen super austenitic stainless steel block is observed under a metallurgical optical microscope at 139 times, and it is found that all are located in the columnar crystal zone. Therefore, the correction coefficient β is taken as 1.1. Then, the mildly corroded steel block is remade according to step (1).

[0048] The ratio of V 硝酸 : V 盐酸 is calculated to be 0.06 through empirical formula (1), where N 含 is 1.00. Generally, V 盐酸 is taken as 100 ml. Therefore, V 硝酸6.0ml. Then, according to the concentration requirements of each component of the corrosive agent, 0.127g of oxalic acid, 0.848g of ferric chloride, 1.06g of sodium molybdate and 0.636g of cupric chloride were prepared. The weighed nitric acid, ferric chloride, oxalic acid, sodium molybdate and cupric chloride were added to the hydrochloric acid in turn and stirred continuously with a glass rod to fully dissolve them. Then, the solution was placed in a 50°C constant temperature water bath heating box for full reaction. After 19 minutes, the solution turned light yellow-green, indicating that the basic reaction of the solution was completed.

[0049] Clamp the prepared steel block with a clamp and immerse it in the corrosive agent in the constant temperature water bath heating box. Shake it gently to prevent bubbles from adhering to the surface of the steel block. Then calculate the required constant temperature water bath heating corrosion time as 1214.4 seconds using formula (2), where Ni 含 , Mo 含 , N 含 , Mn 含 It can be concluded from Table 1. The initial temperature of the constant temperature water bath heating box during corrosion was set to 80°C according to experience, and the water bath temperature was lowered to 48°C after 500s. After the corrosion was completed, the steel block was taken out and rinsed with deionized water and anhydrous ethanol in turn, and finally air-dried with an air dryer. The corroded steel block was photographed and observed with a metallographic optical microscope at a magnification of 139 times. The dendrites of the steel block were as follows Figure 2 As shown. Figure 2 The primary and secondary dendrites of the steel block can be clearly observed, and the corrosion effect is uniform, complete and clear. It can be used to preliminarily analyze the mechanical properties and uniformity of high nitrogen super austenitic stainless steel blocks, and can also be used to count the secondary dendrite spacing.

[0050] Example 3

[0051] The element contents of the high nitrogen super austenitic stainless steel block in this embodiment are shown in Table 3.

[0052] Table 3 Composition content of high nitrogen super austenitic stainless steel block (wt%)

[0053] Component Cr Mn Ni Mo C Si Cu N Fe Content 24.5 6.00 17.0 5.50 0.02 0.40 0.50 0.60 Balance

[0054] The preparation of high nitrogen super austenitic stainless steel block and the preparation of slight corrosive agent are the same as above. After slight corrosion, it is observed through a 139x optical metallographic microscope. Most of the steel block is located in the columnar crystal area, and a small part is located in the equiaxed crystal area. Therefore, the correction coefficient β is taken as 1.04.

[0055] Then calculate V using the empirical formula (1) 硝酸 :V 盐酸 The ratio is 0.036, where N 含 is 0.60, generally V 盐酸 is 100ml, so V 硝酸The weight of the nitric acid, ferric chloride, oxalic acid, sodium molybdate and cupric chloride was added to the hydrochloric acid in turn and stirred with a glass rod to fully dissolve. The solution was then placed in a 50°C constant temperature water bath heating box for full reaction. After 20 minutes, the solution turned light yellow-green, indicating that the basic reaction of the solution was completed.

[0056] The corrosion time was calculated as 981.76 seconds using the empirical formula (2). The initial temperature of the constant temperature water bath was set to 80°C based on experience during corrosion, and the water bath temperature was lowered to 49°C after 500 seconds. The corrosion operation was the same as above. After the corrosion was completed, the corroded steel block was photographed and observed using a metallographic optical microscope at a magnification of 139 times. The dendrites of the steel block were as follows: Figure 3 As shown. Figure 3 The primary and secondary dendrites of the steel block can be clearly observed, and the corrosion effect is uniform, complete and clear. It can be used to preliminarily analyze the mechanical properties and uniformity of high nitrogen super austenitic stainless steel blocks, and can also be used to count the secondary dendrite spacing.

[0057] Example 4

[0058] The element contents of the high nitrogen super austenitic stainless steel block in this embodiment are shown in Table 4.

[0059] Table 4 Composition content of 654 steel high nitrogen super austenitic stainless steel block (wt%)

[0060] Component Cr Mn Ni Mo C Si Cu N Fe Content 24.5 4.00 15.0 5.50 0.02 0.40 0.50 0.40 Balance

[0061] The preparation of high nitrogen super austenitic stainless steel block and the preparation of slight corrosive agent are the same as above. After slight corrosion, it is observed through a 139x optical metallographic microscope. Most of the steel block is located in the columnar crystal area, and a small part is located in the equiaxed crystal area. Therefore, the correction coefficient β is taken as 1.04.

[0062] Then calculate V using the empirical formula (1) 硝酸 :V 盐酸 The ratio is 0.024, where N 含 is 0.40, generally V 盐酸 is 100ml, so V 硝酸 Then, according to the concentration requirements of each component of the etchant, 0.126g of oxalic acid, 0.838g of ferric chloride, 1.048g of sodium molybdate and 0.629g of cupric chloride were prepared. The rest of the solution preparation process was the same as above.

[0063] The corrosion time is calculated as 795.6 seconds by the empirical formula (2). The initial temperature of the constant-temperature water bath heating box during corrosion is set at 81°C according to experience, and the water bath temperature is lowered to 49°C after 500 seconds. The corrosion operation is the same as above. After corrosion, the corroded steel block is photographed and observed with a metallographic optical microscope at a magnification of 139 times. The dendrites of the steel block are as Figure 4 shown. It can be clearly observed from Figure 4 the primary dendrites and secondary dendrites of the steel block, and the corrosion effect is uniform, complete and clear. It can be used for the preliminary analysis of the mechanical properties and uniformity of the high-nitrogen super-austenitic stainless steel block, and can also be used for counting the secondary dendrite spacing.

[0064] Example 5

[0065] In this example, the element content of the high-nitrogen super-austenitic stainless steel block is shown in Table 5

[0066] Table 5 Composition content (wt%) of high-nitrogen super-austenitic stainless steel block

[0067] Component Cr Mn Ni Mo C Si Cu N Fe Content 24.5 6.00 19.0 6.50 0.02 0.40 0.50 0.80 Balance

[0068] The preparation of the high-nitrogen super-austenitic stainless steel block and the preparation of the mild corrosion agent are the same as above. After mild corrosion, it is observed through a 139-fold metallographic optical microscope. Since the steel block is completely located in the CET region, the correction coefficient β is taken as 1.0.

[0069] Then, V is calculated through the empirical formula (1) 硝酸 : The ratio of V 盐酸 is 0.048, where N 含 is 0.80. Generally, V 盐酸 is taken as 100 ml. Therefore, V 硝酸 is 4.8 ml. Then, 0.127 g of oxalic acid, 0.848 g of ferric chloride, 1.06 g of sodium molybdate and 0.636 g of copper chloride are prepared according to the concentration requirements of each component of the corrosion agent. The remaining operations for preparing the solution are the same as above.

[0070] The corrosion time is calculated as 1119 seconds by the empirical formula (2). The initial temperature of the constant-temperature water bath heating box during corrosion is set at 81°C according to experience, and the water bath temperature is lowered to 51°C after 501 seconds. The corrosion operation is the same as above. After corrosion, the corroded steel block is photographed and observed with a metallographic optical microscope at a magnification of 139 times. The dendrites of the steel block are as Figure 5 shown. It can be clearly observed from Figure 5 the primary dendrites and secondary dendrites of the steel block, and the corrosion effect is uniform, complete and clear. It can be used for the preliminary analysis of the mechanical properties and uniformity of the high-nitrogen super-austenitic stainless steel block, and can also be used for counting the secondary dendrite spacing.

[0071] Example 6

[0072] In this embodiment, the elemental content of the high-nitrogen super-austenitic stainless steel block is shown in Table VI

[0073] Table VI Composition content (wt%) of 654 steel high-nitrogen super-austenitic stainless steel block

[0074] Component Cr Mn Ni Mo C Si Cu N Fe Content 24.5 5.00 15.0 6.50 0.02 0.40 0.50 1.00 Balance

[0075] The preparation of the high-nitrogen super-austenitic stainless steel block and the preparation of the mild etchant are the same as above. After mild etching, it is observed through a metallographic optical microscope at 139 times magnification. The steel block is mainly composed of an equiaxed crystal region. Therefore, the correction coefficient β is taken as 0.9.

[0076] Then, V is calculated through the empirical formula (1) 硝酸 : V 盐酸 The ratio of is 0.06, where N 含 is 1.0. Generally, V 盐酸 is taken as 100 ml. Therefore, V 硝酸 is 6.0 ml. Then, 0.127 g of oxalic acid, 0.848 g of ferric chloride, 1.06 g of sodium molybdate, and 0.636 g of copper chloride are prepared according to the concentration requirements of each component of the etchant. The remaining operations for preparing the solution are the same as above.

[0077] The etching time is calculated to be 1014.3 seconds through the empirical formula (2). The initial temperature of the constant-temperature water bath heating box during etching is set to 80 °C according to experience, and the water bath temperature is lowered to 49 °C after 502 seconds. The etching operation is also the same as above. After etching, the etched steel block is photographed and observed with a metallographic optical microscope at a magnification of 139 times. The dendrites of the steel block are as Figure 6 shown. From Figure 6 it can be clearly observed the primary dendrites and secondary dendrites of the steel block. The etching effect is uniform, complete, and clear. It can be used for the preliminary analysis of the mechanical properties and uniformity of the high-nitrogen super-austenitic stainless steel block, and can also be used for statistical analysis of the secondary dendrite spacing.

[0078] Example 7

[0079] In this embodiment, the elemental content of the high-nitrogen super-austenitic stainless steel block is shown in Table VII

[0080] Table VII Composition content (wt%) of 654 steel high-nitrogen super-austenitic stainless steel block

[0081] Component Cr Mn Ni Mo C Si Cu N Fe Content 24.5 7.00 15.0 7.50 0.02 0.40 0.50 0.40 Balance

[0082] The preparation of the high-nitrogen super-austenitic stainless steel block and the preparation of the mild etchant are the same as above. After mild etching, it is observed through a metallographic optical microscope at 139 times magnification. The steel block is mainly composed of an equiaxed crystal region. Therefore, the correction coefficient β is taken as 0.9.

[0083] Then, V is calculated through the empirical formula (1) 硝酸 : V盐酸 The ratio is 0.024, where N 含 is 0.40. Generally, V 盐酸 is taken as 100 ml. Therefore, V 硝酸 is 2.40 ml. Then, 0.123 g of oxalic acid, 0.819 g of ferric chloride, 1.024 g of sodium molybdate, and 0.614 g of copper chloride are prepared according to the concentration requirements of each component of the etchant. The remaining operations for preparing the solution are the same as above.

[0084] The etching time is calculated to be 813.6 seconds through the empirical formula (2). The initial temperature of the constant-temperature water bath heating box during etching is set to 81°C according to experience, and the water bath temperature is lowered to 48°C after 499 seconds. The etching operation is also the same as above. After the etching is completed, the etched steel block is photographed and observed with a metallographic optical microscope at a magnification of 139 times. The dendrites of the steel block are as Figure 7 shown. From Figure 7 it can be clearly observed the primary dendrites and secondary dendrites of the steel block. The etching effect is uniform, complete, and clear. It can be used for the preliminary analysis of the mechanical properties and uniformity of the high-nitrogen super-austenitic stainless steel block, and can also be used to count the secondary dendrite arm spacing.

Claims

1. A high nitrogen super austenitic stainless steel cast dendrite etchant, characterized in that: The etchant is a mixed solution of nitric acid, hydrochloric acid, oxalic acid, ferric chloride, sodium molybdate and cupric chloride, wherein: the concentrations of oxalic acid and ferric chloride are fixed at 1.1-1.3 g / L and 7.5-8.5 g / L; the concentrations of sodium molybdate and cupric chloride are 9.0-11.0 g / L and 6.0-7.0 g / L; the mass percentage concentrations of nitric acid and hydrochloric acid are 65-68% and 36-38% respectively, and the ratio of nitric acid to hydrochloric acid is determined according to the nitrogen content in the steel, which is obtained by formula (1): V 硝酸 :V 盐酸 =0.06N 含 (1) Where V 硝酸 and V 盐酸 are the volumes of nitric acid and hydrochloric acid in the corrosive agent, N 含 is the nitrogen solubility in the steel block.

2. The high nitrogen super austenitic stainless steel cast dendrite etchant according to claim 1, characterized in that: The composition range of the high nitrogen super austenitic stainless steel is: C: ≤0.12%, Si: ≤0.71%, Mn: 3.0-11.0%, Cr: 16.0-25.0%, Mo: 4.0-10.0%, N: 0.3-1.6%, Ni: 14.0-23.0%, Cu: 0.2-0.6%, Fe: balance.

3. The high nitrogen super austenitic stainless steel cast dendrite etchant according to claim 1, characterized in that: The composition range of the high nitrogen super austenitic stainless steel is: C: 0.02%, Si: ≤0.71%, Mn: 3.0-11.0%, Cr: 16.0-25.0%, Mo: 4.0-10.0%, N: 0.3-1.6%, Ni: 14.0-23.0%, Cu: 0.2-0.6%, Fe: balance.

4. The method for using the high nitrogen super austenitic stainless steel cast dendrite etchant according to claim 2 or 3, characterized in that: The following steps are involved: (1) Preparation of high nitrogen super austenitic stainless steel blocks The corroded high nitrogen super austenitic stainless steel block was hot mounted with a mounting machine, and then ground and polished with sandpaper and a polishing machine in sequence until the surface was smooth and shiny; then rinsed with deionized water and anhydrous ethanol and dried, and finally observed with an optical metallographic microscope to ensure that there were no scratches or dents on the surface; (2) Determine the correction factor β The correction factor β is determined by the condition of the crystal area after slight corrosion; In case of slight corrosion, the corrosive agent is prepared by 7% to 9% perchloric acid by volume and 91% to 93% anhydrous ethanol by volume, and the mass percentage concentration of perchloric acid is 70% to 72%; The prepared mild corrosive agent is allowed to react for 3 to 5 minutes, and then the prepared high nitrogen super austenitic stainless steel block is immersed in the mild corrosive agent, the constant temperature environment is set to 78 to 80° C., and the corrosion time is 50 to 70 seconds; after the corrosion is completed, the steel block is taken out and rinsed and dried with deionized water and anhydrous ethanol in turn; the high nitrogen super austenitic stainless steel block after mild corrosion is placed under a metallographic optical microscope to observe the crystal area characteristics, and then determine the correction coefficient β; and the mildly corroded steel block is remade according to step (1); (3) Preparation of high nitrogen super austenitic stainless steel cast dendrite etchant Add nitric acid, ferric chloride, oxalic acid, sodium molybdate and cupric chloride to hydrochloric acid in sequence, stir thoroughly, and place the obtained solution in a constant temperature environment of 48-52°C for a full reaction for 15-20 minutes. When the solution turns light yellow-green, it means that the solution reaction is complete, and a high-nitrogen super austenitic stainless steel cast dendrite corrosive agent is obtained; (4) Determine the constant temperature heating corrosion time T The constant temperature heating corrosion time T is calculated by formula (2): T=(18Ni 含 +38Mo 含 +505N 含 +21Mn 含 )×β (2) Where Ni 含 、Mo 含 、N 含 , Mn 含 are the solubility of the element in the steel block, respectively. The correction factor β has been calculated in step (2); (5) Metallographic corrosion Immerse a high-nitrogen super austenitic stainless steel block in a corrosive agent in a constant temperature environment and shake it gently to prevent bubbles from adhering to the surface of the steel block. After the corrosion is completed, take out the steel block and rinse it thoroughly with deionized water and anhydrous ethanol in turn, and blow it dry. Use a scanning electron microscope (SEM) or a metallographic optical microscope to observe its dendrite structure.

5. The method for using the high nitrogen super austenitic stainless steel cast dendrite etchant according to 4, characterized in that: In step (2), the correction coefficient β is 0.9 to 1.1; when the steel block is located in the columnar crystal region, it is 1.1; when it is located in the CET region, it is 1.0; and when it is located in the equiaxed crystal region, it is 0.

9.

6. The method for using the high nitrogen super austenitic stainless steel cast dendrite etchant according to 4, characterized in that: In step (5), the initial temperature of the constant temperature environment during corrosion is set to 78-80°C to accelerate the corrosion efficiency. The corrosion time at this temperature is about 490-510s. The temperature is then set to 48-50°C until the corrosion is completed to ensure a good corrosion effect.

Citation Information

Patent Citations

  • Dendritic crystal corroding agent for high nitrogen austenitic stainless steel and preparation method thereof

    CN106596235A

  • High-nitrogen austenitic stainless steel corrosive agent and corrosion method

    CN118360654A